เขตอำนาจรัฐทางอาญาของรัฐผู้ให้สัญชาติอากาศยาน - ทัศนีย์ จรรยาชูกุล (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objectives to implement the aircraft nationality principle is to establish the relationship between State of Registration and aircraft as well as the legal status to an aircraft. Such implementation originates the significant legal consequences. Firstly, the State of Registration has power, duty and responsibility on their registered aircraft. Secondly, the State of Registration has the right to exercise the criminal jurisdiction over such registered aircraft. In case of civil aircraft, the State of Registration is not the one who can exercise the criminal jurisdiction over their registered aircraft. Therefore, this thesis is intended to study on problems concerned with criminal jurisdiction over civil aircraft only. Even there is the aircraft nationality principle governs criminal jurisdiction over aircraft, but there still are some problems on criminal jurisdiction over some types of aircraft;Flag of Convenience Aircraft, Interchange of Aircraft, Aircraft of the International Organization, Aircraft ofthe Joint Air Transport Operating Organizations and Aircraft of the Internation Operating Agencies. From the research, it has been found that such problems caused by the weak points of international law regarding the aircraft nationality principle which is Chicago Convention 1944 that empowered the State to considered the nationality to aircraft without contemplation on genuine link and also stated that only State can give the nationality to aircraft. Moreover, these problems resulted from lacking of explicit regulations and legal sanctions of international law regarding the criminal jurisdiction over aircraft principle which are Tokyo Convention 1963, Hauge Convention 1970 and Montreal Convention 1971. The author has summarized and recommened some possible resolutions with regard to problems on both International and Thai Law.